Chinese Christianity : an interplay between global and local perspectives - Wu, Ziming (Religion in Chinese societies, 2012)
Viewing Chinese Christianity from a globalization perspective, this volume describes the interplay of "universal" and "particular" aspects as well as the global and local forces which shaped the characteristics of Chinese Christianity.